Analysis of Lingual Arch Form in Dental Students of Nepal with Normal Occlusion - Kafle D; Devagiri V; Chaudhari PK; Mishra RK (Dove Medical Press, 2020)
Dashrath Kafle,1 Vasant Devagiri,2 Prabhat Kumar Chaudhari,3 Rajeev Kumar Mishra1 1Department of Orthodontics, Kathmandu University School of Medical Sciences, Dhulikhel, Bagmati, Nepal; 2Department of Orthodontics, College of Medical Sciences, Kathmandu University, Bharatpur, Bagmati, Nepal; 3Division of Orthodontics and Dentofacial Deformities, All India Institute of Medical Sciences, New Delhi, Delhi, IndiaCorrespondence: Rajeev Kumar MishraKathmandu University School Of Medical Sciences, Dhulikhel, Bagmati, NepalTel +977-9817852166Email mishra.rkm84@gmail.comBackground: The objectives of this study were to describe and classify lingual arch form in dental students with normal occlusion and explore the possibility to provide a lingual arch form template for Nepalese population.Methods: The occlusion and arch form of 220 undergraduate dental students were analyzed and thirty-three subjects (14 males, 19 females) fulfilling the inclusion criteria were selected for the study. Reference points were drawn on the lingual surfaces of the teeth of study model using an indelible marker. A transparent ruled grid was used to obtain x and y coordinate values of the reference point. Following distances were measured with a digital caliper: inter-canine width, inter-molar width, inter-second molar width, canine depth, first molar depth, and second molar depth. Two-step cluster analysis was used to further classify the arch. The mean reference point values of each cluster were entered into the software (CurveExpert 1.4, Hymas developers). The curve finder tool of the software was used to obtain the curve which best described the arch forms.Results: Two-step cluster analysis identified two distinguished clusters of lingual arch forms. Tenth degree polynomial was chosen as the best possible fit for lingual arch forms by using Curvefinder tool of the software CurveExpert 1.4.Conclusion: Two types of anatomical lingual arch forms derived from Nepalese dental students with normal occlusion have been described and templates for the same have been generated.Keywords: lingual arch form, lingual orthodontics, cluster analysis, normal occlusion, polynomial